A COMPARATIVE STUDY OF THE COLONIAL DECLINE OF THE INDIAN TEXTILE INDUSTRY AND ITS REVIVAL UNDER THE SWADESHI MOVEMENT - Jayswal, Bablu Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
This paper presents a comparative analysis of the causes of the colonial decline of the Indian textile industry and its revival efforts under the Swadeshi Movement. The main argument of this study is that British discriminatory tariff policies and free trade pushed Indian weavers into a severe phase of deindustrialization, placing immense pressure on the rural economy. In contrast, the Swadeshi Movement, which began after 1905, offered ideological resistance to this decline, particularly through the political symbolism of the spinning wheel and khadi. Although Swadeshi efforts did not completely reverse the damage to the rural economy, they strengthened national identity and boosted the Indian mill industry. This research establishes that the textile industry, rather than being merely an economic commodity, became a political weapon of resistance for Indian nationalism, laying the foundation for a limited but significant economic revival in the face of colonial devastation.